Enhancement of the photoluminescence modulation ratio in highly transparent KNN-based ceramics for optical information storage. Issue 14 (23rd March 2023) - Wang, Yaqi; Guo, Pengkun; Wang, Yanan; Huo, Nengmeng; Sun, Ruyi; Zhang, Yongcheng; Zhang, Jun-Cheng; Qin, Yalin
Abstract : The combination of high transmittance and large switching contrast in transmittance and photoluminescence intensity make the K0.5 Na0.5 NbO3 – x Pr ceramics promising for optical information storage and optical switch applications. Abstract : Transparent photochromic materials have attracted extensive attention in applications of optical information storage and optical switches, in which both high transparency and large switching contrast are required. In this work, K0.5 Na0.5 NbO3 – x Pr ( x = 1.0, 2.0, 2.5, 3.0) ceramics were prepared by pressure-less sintering. When x ≥ 2.0, high transmittances ( T ) were achieved due to the small grain size and the highly symmetrical phase structure. Optimal transmittances of ∼72.9% at 900 nm and ∼73.9% at 2500 nm were obtained in the K0.5 Na0.5 NbO3 –3Pr ceramic. The transmittance and photoluminescence intensity can be obviously modulated by photochromism and have been found to be closely related to the Pr doping amount. A high modulation ratio of luminescence intensity (Δ R L ) of ∼ 81% was obtained by illumination in the transparent K0.5 Na0.5 NbO3 –3Pr ceramic (with T ∼ 72.9% at 900 nm), while a modulation ratio of transmittance (Δ R T ) of 29% was achieved in the transparent K0.5 Na0.5 NbO3 –2Pr ceramic (with T ∼ 63.3% at 900 nm). The transmittance and photoluminescence intensity recover to the original state by heating and both the Δ R T and Δ R L show good stability when the ceramics are alternately modulated by illumination and thermal stimulation. The combination of high transparency and large switching contrast makes Pr-doped K0.5 Na0.5 NbO3 ceramics promising for optical information storage and optical switch applications.